Students' perception of lecturers performance at the International Islamic University Malaysia, Department of Business Administration - Bawah, Mohammed; Wan Nasir, Zaireena (Management Academic Research Society, 2021)
This study investigated the impact of students’ perception on lecturers’ performance in class. The aim of the study was to assess lecturers’ performance in lecturing various courses using students’ perception as an indicator of lecturers’ performance. The study utilized a random sampling research design method with the target population of third and fourth year students. Stratified sampling technique was used to arrive at the study sample of 100 students. A specifically designed instrument, the Students’ Perceptions of Performance Scales (SPTPS) was used to gather data. The exploratory factor analysis and confirmatory factor analysis methods were conducted to validate the performance constructs. The results of the analysis shows that, the relationship between the attitude of lecturers and performance in class and the relationship between methodology and lectures’ performance in class are all positive. However, the study rejected relationship between knowledge of lecturers and lecturers’ performance in class. The study therefore, concluded that, there are aspects of lecturers’ performance in class that are less than excellent and in need of further improvement.